Tranexamic acid inhibits group A streptococci–mediated fibrinolysis in vitro and modulates host immune cells in vivo - Possehl, Maresa; Vasudevan, Praveen; Schenk, Sonja; Maletzki, Claudia; David, Robert; Kreikemeyer, Bernd; Oehmcke-Hecht, Sonja (Frontiers in Immunology, 2025)
Group A Streptococcus (GAS) exploits the host fibrinolytic system by activating plasminogen via streptokinase, promoting clot degradation, tissue invasion, and immune evasion. Tranexamic acid (TXA), a clinically used antifibrinolytic agent, inhibits fibrinolysis, but its impact on GAS virulence and host immune responses remains incompletely understood. We investigated whether clinically relevant concentrations of TXA or ϵ-aminocaproic acid (AHA) inhibit GAS-induced fibrinolysis, affect bacterial survival in blood, and modulate host immune responses. In vitro plasma clot lysis assays, D-dimer quantification, and bacterial escape experiments were used to assess fibrinolytic activity. Western blots and substrate assays evaluated plasminogen and fibrinogen binding and plasmin activity. Bacterial survival and immune phenotypes were analyzed in human blood, and in vivo responses were assessed in a murine intranasal infection model. TXA at therapeutic concentrations (10–50 µg/ml) blocked streptokinase- and GAS-induced fibrinolysis, reduced D-dimer release, and prevented bacterial escape from clots in vitro. It impaired GAS survival in whole human blood without affecting growth in plasma or culture medium, suggesting a host-mediated effect. TXA affected plasminogen interaction with the bacterial surface and reduced fibrinogen degradation, suggesting interference in GAS-driven fibrinolysis. In infected blood, TXA partially restored CD169 and CD66b expression, consistent with preserved monocyte and neutrophil activation. In vivo, TXA lowered lung IL1β and shifted cardiac macrophage polarization toward more M1 and fewer M2 cells. These findings indicate that TXA not only inhibits GAS-induced fibrinolysis but also enhances innate immune responses, exerting both antifibrinolytic and immunomodulatory effects during infection.